y(8-2)+6=15

Simple and best practice solution for y(8-2)+6=15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y(8-2)+6=15 equation:


Simplifying
y(8 + -2) + 6 = 15

Combine like terms: 8 + -2 = 6
y(6) + 6 = 15

Reorder the terms for easier multiplication:
6y + 6 = 15

Reorder the terms:
6 + 6y = 15

Solving
6 + 6y = 15

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 6y = 15 + -6

Combine like terms: 6 + -6 = 0
0 + 6y = 15 + -6
6y = 15 + -6

Combine like terms: 15 + -6 = 9
6y = 9

Divide each side by '6'.
y = 1.5

Simplifying
y = 1.5

See similar equations:

| -3x=x+7-4 | | 2x+3(x+1)=2(x+3)+7 | | 4/x-7/5x=-/12 | | 12-2(x-4)=3(x+2)-11 | | 7t-51=96 | | -8+y=9 | | 200x^2+300x-80=0 | | -9=w-7 | | 5-12/a=5/3 | | 6+b=38 | | 2y=8x+x+7 | | 12x-5+7x-5=180 | | 1/2x-9=-11 | | 4(3x+2)=-5(5x-2)+2x | | 20x+5=24-12x | | Y=log(-3x) | | 2x+3x+5x=y | | 5x+4=x+4(2+x) | | 60x+45=285 | | 3x+17=9-5x | | 9/25-y=-1/4 | | 8x-(2x-9)=4x-(8+4x) | | y-4-7y-3= | | .69x+19=43 | | y/4=5/13 | | 675x+125=3175 | | 3y^3-2y=x-3 | | 55x+850=123 | | y-1=2/3(x=9) | | x*10+12*8=196 | | 10=y+z | | x/2-=1 |

Equations solver categories